Human Immunodeficiency Virus Type 1 Vif Up-Regulates the Expression of Tat via AKT Signaling Pathway: Role of Ubiquitin Specific Protease 17 - Lata, Sneh; Sood, Vikas; Banerjea, Akhil C. (Frontiers in Microbiology, 2022)
Human Immunodeficiency Virus-1 (HIV-1) has RNA genome and depends on host cellular machinery for most of its activities. Host cellular proteins modulate the expression and activity of viral proteins to combat the virus. HIV-1 proteins are known to regulate each other for the benefit of virus by exploiting these modulations. Here, we report that HIV-1 Vif increases the expression of Tat via AKT signaling pathway. We show that HIV-1 Vif activates AKT signaling pathway by inducing phosphorylation of AKT. Mdm2, downstream target of AKT signaling, increases the expression of Tat protein in ubiquitin-dependent manner by inducing the expression levels of USP17 which is a deubiquitinase (DUB) and stabilizes Tat protein. Thus, HIV-1 proteins exploit AKT signaling pathway to promote viral replication.